Corpos em protesto: análise discursiva do movimento Femen - Pereira, Fernanda (2017)
According to the french Discourse Analysis (AD), formulated by Michel Pêcheux, discourse is an effect of meaning among interlocutors, a meaning that occurs within a given discursive formation (FD), and determines what can and should be said. In a society already used to the historical struggle of the Feminist Movements for equal rights and in which the body (both male and female) is exploited commercially, daily, by the media, it seems strange that the exposure of the half naked female body in protests, is still percieved as offensive and negative. The feminist group FEMEN, which fights against patriarchy in its three forms (materialized, according to the group, in sexual exploitation of women, dictatorships and major religions), is constantly attacked, during its protests, by exposing their half-naked bodies. Through the identification of the elements used by the activists in their protests and the analysis of the statements that “dress” their bodies, this work aims to understand how the discursive memory is reclaimed, producing meaning. Thus, this dissertation seeks to understand the discursive processes that allow the production of these effects of meaning, and how the naked body constitutes itself as a discursive materiality, displacing the bodies of the activists from the ideal of femininity (according to Kehl (2016)) or submission, docility, with the sole purpose of maternity) built throughout the nineteenth century. Through the analysis of the images of three protests, which question the control exercised over the female bodies, by the main religions of the Western world, this work aims to understand how the naked female body, when used as a vehicle of protest, produces effects of meaning that break up with the current FD that determines what a woman can and should be, within the ideals that persist in our society. In this sense, the naked body, when used to denounce and question control practices over the women’s body, produces discomfort, estrangement, rupture with these discourses.